Using a clinical decision‐making framework to foster sonographer student learning in the clinical setting. Issue 4 (20th September 2016) - Thoirs, K.; Sim, J.
Abstract: Sonographers in clinical education roles have an important role in developing clinical skills in sonography students. These skills include technical (psychomotor) skills, image interpretation skills and clinical decision‐making (CDM) skills. CDM in clinical practice is important for the quality of clinical services. Although, there is well developed and a growing body of knowledge on CDM in the health and medical literature, there is a paucity of information that sonographers or sonography students can draw on to facilitate the development of decision‐making skills in the clinical setting. We postulate that a framework or model of CDM can be useful in teaching and evaluating critical thinking and clinical reasoning in sonography students. CDM frameworks can help students and their supervisors organise their learning to solve clinical questions by providing guidance, organisation and sequencing of learning experiences, scaffolding of learning, building of existing knowledge and skills through new real life experiences and promotion of deep learning. This paper outlines and discusses the elements of a CDM framework and how it can be used to in the clinical setting to develop CDM skills and provide a structure for clinical teaching.